"Factors Affecting The Timing Of The Issuance Of Financial Statements For The Semi-Annual Industrial And Service Companies Listed In Amman Stock Exchange "An Empirical Study - Fares, Iyad Jamal; Al Atili, Manal Abdul Rahman; Abu Zar, Imran Ishaq (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to uncover the factors that affect the timing of issuing semi-annual financial statements through the industrial and service companies listed on the Amman Stock Exchange during the years 2007-2008. The five hypothesis hypotheses were examined. Company performance, company life, company size and company’s financial leverage. The dependent variable was the timing of the issuance of the semi-annual financial statements. The results showed no statistically significant relationship with the hypotheses of the study. There was also no statistically significant relation with the financial increase and performance. However, there was a statistically significant relationship with profitability, age, size, and also the absence of a statistically significant relation with the financial leverage, the existence of a statistically significant relationship with profitability, and the group that publishes the financial statements from the forty-sixth day, and that most of the groups have no statistically significant relation to the study hypotheses. The results also indicated that the integration of groups, (0+1) is the period from which the financial statements are issued from the first to the thirtieth day. There is no statistically significant relationship with the financial increase, size and performance. However, there was a statistically significant relationship with age and profitability. The group (2 + 3) Which issues financial statements from today For thirty or more, the absence of a statistically significant relationship to the hypotheses of the study.